Identification and comparative transcriptome analyses between resistant and susceptible soybean varieties in response to soybean mosaic virus and cowpea mild mottle virus infection - Li, Huajuan; Dong, Zhimin; Xu, Manru; Shang, Jiahui; Feng, Xiuli; Chen, Jianping; Sun, Zongtao; Wei, Zhongyan (Phytopathology Research, 2025)
Soybean is an important oil and cash crop around the world, but viral infections are widespread in soybean producing area, causes significant damage in soybean. However, the resistance mechanisms of soybean to viral diseases remain poorly understood. In this study, we evaluated resistance to soybean mosaic virus (SMV; Potyvirus glycitessellati) and cowpea mild mottle virus (CPMMV; Carlavirus vignae) in 120 soybean varieties collected from three major soybean production areas. Resistance evaluation revealed that 40% of the tested varieties exhibited resistance to SMV. In contrast, resistance to the emerging CPMMV was generally weak, with fewer than 5% of varieties showing resistance. Notably, five resistant varieties displayed dual resistance to both SMV and CPMMV, although WS1015 exhibited mild resistance to both viruses. RT-qPCR and Western blot confirmed that resistant varieties had significantly lower viral accumulation compared to susceptible controls. RNA sequencing (RNA-seq) analysis highlighted significant differences in the transcriptional responses of resistant and susceptible varieties to SMV and CPMMV infections. The resistant varieties exhibited relatively stable gene expression patterns, with upregulation of genes associated with defense responses, metabolite biosynthesis, and lignin biosynthesis. In contrast, the susceptible varieties showed a broader upregulation of genes, particularly those involved in broad-spectrum immune responses such as jasmonic acid (JA) signaling and reactive oxygen species (ROS) production. Overall, this study provides valuable insights into the molecular mechanisms underlying resistance to SMV and CPMMV in soybean, contributing to the advancement of resistance breeding strategies.